On Some Classes of Invariant Submanifolds of \((k,μ)\)-Contact Manifolds - Siddesha, M. S.; Bagewadi, C. S. (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we study invariant submanifolds of \((k,μ)\)-contact manifolds. We consider pseudoparallel, 2-pseudoparallel, Ricci-generalized pseudoparallel, 2-Ricci-generalized pseudoparallel submanifolds of \((k,μ)\)-contact manifolds. Further, we search for the conditions \(Z(X,Y)·σ = 0\) and \(Z(X,Y )· ablaσ =0\) on invariant submanifolds of \((k,μ)\)-contact manifolds, where Z is the concircular curvature tensor.